Synthesis of Ag3VO4nanoparticles loaded on Bi2MoO6nanoplates as heterostructure visible light driven photocatalyst by sonochemical method - Phonthep Nualkaew (2018)
©2016 The Ceramic Society of Japan. All rights reserved. Ag3VO4/Bi2MoO6nanocomposites were successfully synthesized by sonochemical method. The as-synthesized products were characterized by X-ray powder diffraction (XRD), field emission scanning electron microscopy (FE-SEM), selected area electron diffraction (SAED), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM). The results revealed the formation of heterostructure Ag3VO4/Bi2MoO6nanocomposites. Photocatalytic activity of the nanocomposites was evaluated through the degradation of rhodamine B (RhB) dye under visible white light irradiation. Among them, heterostructure 10.0 wt% Ag3VO4/Bi2MoO6nanocomposites exhibited the highest photocatalytic activity up to 56.26% for the degradation of RhB dye under visible white light within 240 min.